Original articleDendritic and spinal alterations of neurons from Edinger-Westphal nucleus in Alzheimer’s disease - Mavroudis, Ioannis Asterios; Manani, Marina George; Petrides, Foivos; Petsoglou, Constantina; Njau, Samuel N.; Costa, Vasiliki G.; Baloyannis, Stavros J. (Folia Neuropathologica, 2014)
Alzheimer’s disease (AD) is a heterogeneous neurodegenerative disorder, causing a progressive decline of intellectual faculties, impairment of behavior and social performance, and impairment of speech eloquence, associated with various neurological manifestations based on a variable neuropathological background. Edinger-Westphal nucleus is a selective target of Alzheimer pathology early in the course of the disease. We attempted to determine the morphological alterations of the dendrites and the dendritic spines in Edinger-Westphal nucleus of 7 cases that fulfilled the diagnostic criteria for Alzheimer’s disease. For the histological study, we applied (a) routine neuropathological techniques and (b) rapid Golgi method. We proceeded to 3D neuronal reconstruction for the estimation of dendritic and spinal changes in Alzheimer’s disease. The morphological and morphometric analysis revealed a substantial neuronal loss and synaptic alterations in Edinger-Westphal nucleus in all the cases of Alzheimer’s disease. Distal dendritic branches are prominently affected. The neuronal loss and alteration of the spines in Edinger-Westphal nucleus in Alzheimer’s disease may be related to the exaggerated pupillary reaction to cholinergic antagonists. Furthermore, the vulnerability of distal branches to Alzheimer’s disease might be related to neuroplasticity impairment.